Exploring potentials of sense-making theory for understanding social processes in a public hearing meeting - Lyhne, Ivar (AESOP, 2010)
This paper has point of departure in a planning process for energy infrastructure in Denmark and focuses on a particular public hearing meeting characterised by trenchant opposition and distrust to the authorities among the public. It points at the need to understand the interaction between authorities and the public, which in the case of energy infrastructure, often is characterised by conflict. A sense-making framework is developed based on Karl E. Weick's theory to investigate how participants at the meeting change their understanding of aspects like other actors' opinions and the infrastructure project. Through interviews and observations it is shown that participants' senses do not change except from a few aspects. The participants at the meeting thus seem stuck in their positions without any interest in being open for other interpretations or arguments. The investigation leads to considerations about the benefit and role of such a public meeting and the importance of trust and openness in the social processes in a public hearing.
Book of proceedings: Annual AESOP Congress, 2010 Space is Luxury, Aalto, July 7-10th
Keywords: sense-making; public meeting; infrastructure